Research on the Coordinated Development of Global Urban Economic Competitiveness: Based on a Sample of 1007 Cities - Xiaonan Liu; Pengfei Ni; Fangqu Niu; Bo Li; Qihang Li (Complexity)
Based on the global urban economic competitiveness data in 2017, this study conducts coupling analyses of the competitiveness indicator system. The comprehensive study on the coupling coordination degree among explanatory indexes of urban economic competitiveness concludes that the city with higher economic competitiveness rankings has a higher degree of coupling coordination (DCC); the city ranked lower in the economic competitiveness has a lower DCC. The cities with higher DCC are mainly those global cities or metropolis known for financial and technological innovations, while cities with bare coupling coordination are mainly in underdeveloped countries in Asia, Africa, and Latin America. Based on the findings, the paper employs a model that combines linear regression and quantile regression to identify the specific driving factors that affect the cities’ competitiveness around the world. Therefore, every city should act according to local conditions, focus on the key drivers of urban development, and address the inadequacies to balance the economic development so as to enhance its competitiveness.